A case study of the German archives' labor market in 2019. (22nd June 2021) - Schmerbauch, Maik
Abstract : Purpose: The purpose of this paper is to discuss the German labor market situation. Design/methodology/approach: This study is focusing on the German archive labor market for the year 2019 and examines the job postings. Findings: Many postings in 2019; problems in posts such as different salaries and quality of tasks. Originality/value: This is an original source-based study.